An investigation of thermal behaviour of a machine tool on the dimensional accuracy of parts - Lu, Yuxia; Islam, Mohammad Nazrul (Avestia Publishing, 2012)
The thermal condition of machine tools can profoundly affect the dimensional accuracy of manufactured parts. Consequently, reducing its influence has become increasingly important to modern manufacturing. One of the most convenient and effective ways to reduce thermal error and enhance working accuracy is volumetric error compensation, especially for CNC machine tools. However, currently available compensation methods are highly complicated and difficult to apply in industry. They require a high-precision laser interferometer to measure 21 geometric error components and numerous thermocouples to monitor temperature variations. These requirements make such techniques costly and time consuming. This paper describes the development of a simplified and economical method of compensating for thermally induced errors. Compensation is implemented on the basis of only three axial positioning errors, which are assumed to be functions of ball screw nut temperature and travel distance. Instead of an expensive laser interferometer and many thermocouples, a simple laser Doppler displacement meter and only three thermocouples are required for the proposed method. Results show good agreement between measured and predicted thermally induced errors.